The Changing Memory: How Internet Search Engines Inhibit the Creation of New Ideas - Chrzanowski, Jayden (Journal of Student Research, 2022)
Internet search engines allow people to access new information in seconds. Although the Internet provides easy access to a mass of information, over-reliance on it changes how human memory works, which may have an adverse effect on critical thinking. Individuals with a dependence on search engines tend to remember where they found the information rather than the material itself. Human memory systems work by connecting new information to old in the brain, which requires people to actively think about the material they are taking in. When people bypass critical thinking due to Internet search habits, they cannot form the neural connections needed to create new ideas. As people continue to rely on Internet searches when confronted with a question to which they do not know the answer, abilities to think critically and creatively and to recall information suffer as memory systems change, hindering the ability to generate new ideas.